A Statistical Tool for Time Synchronization Problem in WSN - Upadhyay, D.; Dubey, A.K.; Thilagam, P.S. (Recent Patents on Engineering, 2019)
Background: In recent research, time synchronization has a great importance in the various application of wireless sensor network. Localization, tracking, message passing using contention-based schemes and communication are some of the fields where synchronization between sensor clocks is highly required. Therefore, several algorithms were designed to achieve a rational and reliable frame of time within the wireless sensor network. Patents related to time synchronization in WSN were also analyzed. Methods: This paper discusses the powerful statistical tool using maximum probability theory for synchronizing the time within the sensor's clock. In this paper, maximum probability theory is applied to estimate the best value of clock offset between two sensor clocks. The proposed algorithm is analyzed by exchanging timing messages between nodes using two-way message exchange schemes. Results: The proposed algorithm is also implemented along with a Time-Sync Protocol for Sensor Network. It reduces error deviation from 2.32 to 0.064 ms as compared with Time-Sync Protocol for Sensor Network without proposed works. Conclusion: It was observed that for a small network, proposed work gives better and efficient results with Time-Sync Protocol for Sensor Network.
Keywords: maximum probability theory